2003
DOI: 10.1110/ps.0349703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of S‐sulfonation and S‐thiolation of a novel transthyretin Phe33Cys variant from a patient diagnosed with familial transthyretin amyloidosis

Abstract: Familial transthyretin amyloidosis (ATTR) is an autosomal dominant disorder associated with a variant form of the plasma carrier protein transthyretin (TTR). Amyloid fibrils consisting of variant TTR, wild-type TTR, and TTR fragments deposit in tissues and organs. The diagnosis of ATTR relies on the identification of pathologic TTR variants in plasma of symptomatic individuals who have biopsy proven amyloid disease. Previously, we have developed a mass spectrometry-based approach, in combination with direct DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…No information regarding insulin-glucose homeostasis was reported in either case. In addition to genetic variability, several posttranslationally modified forms of TTR have been identified (33,47,52,63) in serum of healthy humans and in subjects with familial amyloidosis. Future studies are needed to assess whether genetic or posttranslational variants of TTR contribute to elevation of RBP4 and insulin resistance in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…No information regarding insulin-glucose homeostasis was reported in either case. In addition to genetic variability, several posttranslationally modified forms of TTR have been identified (33,47,52,63) in serum of healthy humans and in subjects with familial amyloidosis. Future studies are needed to assess whether genetic or posttranslational variants of TTR contribute to elevation of RBP4 and insulin resistance in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Major spots in Fig. 1 were identified [7,23], but the low-molecular-mass proteins are not well resolved compared to the mass spectrometric results of the corresponding proteins [15][16][17][19][20][21]. The reported MALDI- MS spectra showed that the plasma lipoproteins have been dissociated into their component apolipoproteins, possibly because of the sample treatment with a matrix solution which contains TFA and ACN [19].…”
Section: Maldi-tof-ms Of Human Plasma Treated With Dttmentioning
confidence: 99%
“…However, as far as we know, MS on whole plasma has not been reported. Actually, all the plasma protein studies by MS included complex separation/purification procedures prior to MS analysis, e.g., transthyretin (TTR) was normally purified by immunoprecipitation followed by LC [15][16][17], while apolipoproteins were purified using immunoaffinity chromatography or fractionated by centrifugation [19][20][21]. Electrophoresis 2005Electrophoresis , 26, 2823Electrophoresis -2834 In this paper, we describe a method for direct MALDI-TOF-MS analysis of human plasma proteins without using any prior purification or separation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the occurrence of mixed disulfides with low molecular weight compounds or intramolecular disulfides, determining limited variation in molecular mass of intact proteins, has been revealed by conventional MS procedures. In the case of S-glutathionylated, S-cysteinylglycinylated, Scysteinylated, and S-sulfonated proteins, the occurrence of S-conjugated species has been ascertained by direct electrospray ionization (ESI) measurements of intact proteins, detecting the corresponding adducts presenting a mass difference of +305 Da, +176 Da, +119 Da, and +80 Da, respectively (Hanson et al, 1999;Naito et al, 2000;Lim et al, 2003). As expected, the mass spectra of species containing mixed disulfides were totally affected by reducing agent treatment.…”
Section: Analysis Of Oxidized/nitrosated Products Of Protein Thiolsmentioning
confidence: 71%
“…A careful evaluation of experimental conditions suitable to avoid scrambling phenomena during protein hydrolysis is strongly recommended. Identification of the modified residues has been obtained by liquid chromatography-electrospray ionization (LC-ESI) or matrix-assisted laser desorption ionization (MALDI) mapping experiments by detecting the peptides bearing a mass difference of +305 Da (S-glutathionylated), +176 Da (S-cysteinyl-glycinylated), +119 Da (S-cysteinylated), and +80 Da (Ssulfonated), and eventually confirmed by collision-induced dissociation (CID) measurements (Vilardo et al, 2001;Lim et al, 2003). Similarly, cysteine pairing identification in species containing intra-molecular disulfides as a result of oxidative/nitrosative insult are derived by mass mapping and the tandem mass spectrometry approaches conventionally used for the assignment of disulfides in native polypeptide species.…”
Section: Analysis Of Oxidized/nitrosated Products Of Protein Thiolsmentioning
confidence: 99%